2008
DOI: 10.3174/ajnr.a1360
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Leptomeningeal Hemangioblastomatosis of the Central Nervous System in a Patient with von Hippel-Lindau Disease: Fig 1.

Abstract: SUMMARY:Hemangioblastomas of the central nervous system are the most common tumors seen in patients with von Hippel-Lindau (VHL) disease. A very rare case of diffuse leptomeningeal hemangioblastomatosis obliterating large areas of the subarachnoid space, both intracranial and within the spinal canal, which developed during a relatively short period, in a patient with VHL disease is presented. Von Hippel-Lindau (VHL) disease is an autosomal-dominant disorder (Mendelian Inheritance in Man No. 193300) with a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Literature review revealed only 12 patients reported with cerebrospinal fluid dissemination of cerebellar hemangioblastoma. [ 1 2 3 4 5 6 11 14 15 ] With our report, the total number of patients described in literature would be 14. The demographic characteristics and various other factors been delineated in the Table 1 .…”
Section: Discussionmentioning
confidence: 85%
“…Literature review revealed only 12 patients reported with cerebrospinal fluid dissemination of cerebellar hemangioblastoma. [ 1 2 3 4 5 6 11 14 15 ] With our report, the total number of patients described in literature would be 14. The demographic characteristics and various other factors been delineated in the Table 1 .…”
Section: Discussionmentioning
confidence: 85%
“…There are several case reports and case series in the literature regarding multiple CNS HBs in patients with VHL;[ 7 , 12 , 14 , 18 , 28 , 34 ] however, the dissemination of HB in patients without VHL disease is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…The mutated gene in VHL disease is a tumour suppressor gene located on the short arm of chromosome 3 3 5 6. In addition to HBs, multiple visceral neoplasms are characteristic of VHL disease, including renal clear cell carcinoma, pheochromocytoma and pancreatic neuroendocrine tumour 1 7–11. Although HBs are usually treated with total resection, local recurrence is not uncommon, having a greater frequency of repeat surgery in patients with VHL than in sporadic cases 10…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Mohan et al first described this malignant spread of HB to the spinal cord occurring several years after surgical removal of a cerebellar HB 12. Hemangioblastomatosis has been documented in patients with VHL disease following surgical removal of a cerebellar HB 9 11 13–16. It has also been reported in patients without VHL disease after surgical removal of a cerebellar HB 3 4 8 17–24.…”
Section: Introductionmentioning
confidence: 99%